2005
DOI: 10.1002/ijc.20849
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus latent membrane protein 1 induces the matrix metalloproteinase‐1 promoter via an Ets binding site formed by a single nucleotide polymorphism: Enhanced susceptibility to nasopharyngeal carcinoma

Abstract: The Epstein-Barr Virus (EBV) latent membrane protein 1 (LMP1) has a significant role in several malignancies, including nasopharyngeal carcinoma (NPC). LMP1 is the principal oncoprotein, and we have shown that it also induces a set of factors that mediates invasion, angiogenesis and metastasis. Matrix metalloproteinase-1 (MMP1) is also involved in several malignancies. A single guanine insertion polymorphism (2G) in the MMP1 promoter creates an Ets binding site that causes high levels of transcription and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 46 publications
5
47
0
Order By: Relevance
“…As previously reported, LMP1 transactivates MMP9 production through the activation of NF-nB and activator protein-1 signaling pathways (7). We have also reported that LMP1 promotes cell migration and invasive growth via Ets-1 expression in human epithelial cells (9). These results suggest that the essential binding sites for transactivation of the promoter by LMP1 are, at least in part, gene-specific in epithelial cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As previously reported, LMP1 transactivates MMP9 production through the activation of NF-nB and activator protein-1 signaling pathways (7). We have also reported that LMP1 promotes cell migration and invasive growth via Ets-1 expression in human epithelial cells (9). These results suggest that the essential binding sites for transactivation of the promoter by LMP1 are, at least in part, gene-specific in epithelial cells.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, we reported that induction of Twist by LMP1 is directly associated with the metastatic nature of NPC (8). LMP1 also promotes cell migration and invasive growth via Ets-1 expression (9). In addition, LMP1 induces and causes the release of fibroblast growth factor 2 into extracellular fluid (10).…”
mentioning
confidence: 99%
“…High MMP-1 expression might contribute to the highly malignant nature of NPC. LMP1-positive tumors also overexpressed SPIB, consistent with epithelial cell studies showing that LMP1 induces MMP-1 transcription via ETS transcription factors, such as SPIB (64). In addition, another recent report described a possible link between EBV LMP2A and NPC metastasis (65).…”
Section: Discussionsupporting
confidence: 79%
“…NPCs with high LMP1 expression are reported to show an increased tendency toward metastasis compared with those with low LMP1 expression (12,13,(15)(16)(17)(18). Further, we have produced evidence in recent years that LMP1 can up-regulate multiple invasion, angiogenesis, and metastasis factors, and clarified the molecular mechanisms of their induction (12,13,16,17,(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 93%